A mechanical model to determine the influence of masses and mass distribution on the impact force during running - Liu, W.; Nigg, B. M. (Journal of Biomechanics, 2000)
Simple spring-damper-mass models have been widely used to simulate human locomotion. However, most previous models have not accounted for the effect of non-rigid masses (wobbling masses) on impact forces. A simple mechanical model of the human body developed in this study included the upper and lower bodies with each part represented by a rigid and a wobbling mass. Spring-damper units connected different masses to represent the stiffness and damping between the upper and lower bodies, and between the rigid and wobbling masses. The simulated impact forces were comparable to experimentally measured impact forces. Trends in changes of the impact forces due to changes in touch-down velocity reported in previous studies could be reproduced with the model. Simulated results showed that the impact force peaks increased with increasing rigid or wobbling masses of the lower body. The ratio of mass distribution between the rigid and wobbling mass in the lower body was also shown to affect the impact force peak, for example, the impact force peak increased with increasing rigid contribution. The variation in the masses of upper body was shown to have a minimum effect on the impact force peak, but a great effect on the active force peak (the second peak in the ground reaction force). Future studies on the dynamics and neuro-muscular control of human running are required to take into consideration the influence of individual variation in lower body masses and mass distribution.